The Na+/K+ pump dominates control of glycolysis in hippocampal dentate granule cells - Dylan J Meyer; Carlos Manlio Díaz-García; Nidhi Nathwani; Mahia Rahman; Gary Yellen (eLife, 2022)
Cellular ATP that is consumed to perform energetically expensive tasks must be replenished by new ATP through the activation of metabolism. Neuronal stimulation, an energetically demanding process, transiently activates aerobic glycolysis, but the precise mechanism underlying this glycolysis activation has not been determined. We previously showed that neuronal glycolysis is correlated with Ca2+ influx, but is not activated by feedforward Ca2+ signaling (Díaz-García et al., 2021a). Since ATP-powered Na+ and Ca2+ pumping activities are increased following stimulation to restore ion gradients and are estimated to consume most neuronal ATP, we aimed to determine if they are coupled to neuronal glycolysis activation. By using two-photon imaging of fluorescent biosensors and dyes in dentate granule cell somas of acute mouse hippocampal slices, we observed that production of cytoplasmic NADH, a byproduct of glycolysis, is strongly coupled to changes in intracellular Na+, while intracellular Ca2+ could only increase NADH production if both forward Na+/Ca2+ exchange and Na+/K+ pump activity were intact. Additionally, antidromic stimulation-induced intracellular [Na+] increases were reduced >50% by blocking Ca2+ entry. These results indicate that neuronal glycolysis activation is predominantly a response to an increase in activity of the Na+/K+ pump, which is strongly potentiated by Na+ influx through the Na+/Ca2+ exchanger during extrusion of Ca2+ following stimulation.